2016
DOI: 10.1001/jamacardio.2016.1884
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Fractions With Risks for Coronary Artery Disease and Diabetes

Abstract: Routinely measured lipid fractions exhibit contrasting associations with the risk of CAD and diabetes. Increased LDL-C, HDL-C, and possibly TG levels are associated with a lower risk of diabetes. This information will be relevant to the design of clinical trials of lipid-modifying agents, which should carefully monitor participants for dysglycemia and the incidence of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
212
6
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 265 publications
(265 citation statements)
references
References 34 publications
33
212
6
2
Order By: Relevance
“…Though the study states that this finding was not driven by statin’s effects on HDL, concomitantly there needs to be additional consideration given to statin’s effects on LDL and triglycerides. Since then, another study [34] employed data from genome-wide association studies to investigate the association between lipid fraction and the risk of diabetes using a Mendelian randomization approach that accounted for the pleiotropy of the genetic instruments. This study [34] found that increased LDL, HDL, and possibly triglyceride levels are associated with lowering the risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the study states that this finding was not driven by statin’s effects on HDL, concomitantly there needs to be additional consideration given to statin’s effects on LDL and triglycerides. Since then, another study [34] employed data from genome-wide association studies to investigate the association between lipid fraction and the risk of diabetes using a Mendelian randomization approach that accounted for the pleiotropy of the genetic instruments. This study [34] found that increased LDL, HDL, and possibly triglyceride levels are associated with lowering the risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, another study [34] employed data from genome-wide association studies to investigate the association between lipid fraction and the risk of diabetes using a Mendelian randomization approach that accounted for the pleiotropy of the genetic instruments. This study [34] found that increased LDL, HDL, and possibly triglyceride levels are associated with lowering the risk of diabetes. It should be noted that this study did not directly measure the effects of statins on lipid fractions and development of NODM.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing TC, LDL cholesterol, and TG with a decrease in HDL cholesterol are considered to be risk factors of perinatal complications, in particular placental dysfunction 2,[14][15][16][17][18][19] . …”
Section: Resultsmentioning
confidence: 99%
“…Полученные нами данные согласуются с точкой зрения о связи статин-ассо-циированных нарушений метаболизма глюкозы/инсули-на непосредственно с их гиполипидемическим действи-ем [19] и подтверждают результаты исследований других авторов, показавших, что при наличии не более одного метаболического фактора риска даже на фоне высокой дозы аторвастатина частота новых случаев СД не увеличи-вается, тогда как в случае сочетания нескольких факторов риска встречаемость ассоциированного с приемом ато-рвастатина СД возрастает на 24% [20]. Результаты нашей работы находятся в соответствии с данными ряда крупных рандомизированных клинических исследований, пока-завших связь роста новых случаев СД с исходными мета-болическими нарушениями, в том числе с повышенным уровнем триглицеридов [21], и поддерживают предполо-жение о существовании тесной физиологической взаимос-вязи обратной направленности между уровнем ХС ЛПНП и гликемией [22][23]. Совсем недавно получено новое под-тверждение этой гипотезы: установлено, что ассоциация ряда полиморфизмов гена PCSK9 со сниженным уровнем ХС ЛПНП имеет также взаимосвязь с повышенными зна-чениями базальной гликемии, массы тела и отношения окружности талии к окружности бедер [24].…”
Section: обсуждение основного результата исследованияunclassified